Inventario de recursos turísticos de la comunidad Quinticusig, provincia de Cotopaxi - Cuchiparte Umajinga, Luis Vinicio (2017)
Quinticusig is a small community which lack of information and research of their attractions and its touristic potential. It is about two hours and a half from Latacunga city. Due to the lack of technical information the aims of this research were to validate, register and create the inventory of the natural and cultural attractions. The methodology for this research was the one proposed of the Ministry of Tourism, through some data sheets that included general information of the area it was possible to define the attractions and categories stablishing their ranking. It was necessary to do many field trips. The first step was to talk with the people from the community to find the places with probable potential, their location and main characteristics. The information provided by the habitants of Quinticusig was necessary to define the visits depending on the location and distance of each one. To validate the information provided by the community many field trips were made because direct observation is the main method to do this. The information taken during the field trips was processed in order to complete the inventory sheets, stablishing their categories and finally ranking them. There were 9 attractions between natural and cultural; Among the natives are: Unavana Landscape, Condor Parade, Quinticusig Natural Viewpoint, Ojos de Agua, Moorish Paramo, Tigre Trail, Mortiño Wine Factory and among the cultural ones were the traditional parties and the knowledge of the inhabitants On the use of plants mainly as medicinal. Most of them are ranked number two, which means that they have the potential to become attractions. It could be said that the inventory, categorization and ranking was very useful to motivate the people to commit with the work that is being done in the area and to keep helping with further information. The results were mostly encouraging as the resources found have the potential to become tourist attractions. Therefore, it is recommended that studies on ethnobotany be deepened since it has a potential for development through community tourism. Besides making a general diagnosis of the tourism in the area is important to determine the potential of the attractions according to the different tourist alternatives that can be proposed to practice in the area.